A cell therapy media fill protocol for validation of aseptic processing of cord blood. Issue 10 (2020) - DeDino, Faith; Vincent, Kim; DiNello, Denise; Whitmer, Susan; Adamo, Michelle; Starkey, David; Evans, Kara; Walker, Molly; Thut, Dawn; , Sara Shields; Hof, Wouter Van't
No abstract available